Theoretical Studies on Task-specific Ionic Liquid of 1-(4-Butylamino)-3-methyl Imidazolium Tetrafluoroborate for Capturing CO2 - Yang, Li-Juan; Zhao, Yi; Sun, Wei; Li, Qiang-Wei (Asian Journal of Chemistry, 2012)
Novel task-specific ionic liquids (ILs) of 1-(4-butylamino)-3-methyl imidazolium [Bamim]+ tetrafluoroborate [BF4]– and its reaction with CO2 were systematically studied at B3LYP/6- 311++G** level. Two stable ionic liquids and two molecular complexes from the reactions of those ionic liquids and CO2 were optimized with no imaginary frequencies. The energies including zero point energy and basis sets superimposition energy were calculated. The interactions mechanism between the ion-pairs and the reaction characteristics of ionic liquids and CO2 were analyzed based on natural bond orbital and atom in molecular calculations. The results show that the interactions between ion-pairs are mainly displayed as hydrogen bonds (H-bonds) and they are reinforced by charge dispersion and redistribution of [Bamim]+ and [BF4]–. The interaction energies between ion-pairs are greater than -300 kJ/mol and those between ionic liquid and CO2 are about -10 kJ/mol. The reaction of ionic liquids and CO2 is physical absorption, the molar absorbing ratio is 1:1 and ionic liquid may have a mild regeneration condition theoretically.